Manganese in RR Cotton as Affected by Glyphosate - Rigon, João Paulo Gonsiorkiewicz [UNESP]; Capuani, Silvia [UNESP]; Ferrari Neto, Jayme [UNESP]; Rosolem, Ciro Antonio [UNESP] (Taylor & Francis, 2017)
There is evidence that glyphosate application in soybean tolerant to herbicides could interfere in the manganese (Mn) nutrition of the crop, but there is no information on this effect in cotton plants. This study aimed at assessing manganese accumulation and distribution in cotton as affected by glyphosate application. The experiment was conducted in nutrient solution with four Mn concentrations and two cotton cultivars: conventional NuOpal and NuOpal tolerant to glyphosate (RR). Glyphosate was applied or not to the tolerant cultivar. The inclusion of the glyphosate resistance gene in cotton and herbicide, application increased shikimic acid (ShA) concentration in the plants. Glyphosate application decreased cotton leaf area and the dry matter production of the plant structures. The adverse effects of glyphosate were not overcome with higher Mn rates in the solution.
Keywords: Dry matter; Gossypium hirsutum; Mn uptake; shikimic acid